Komunikasi Suportif Orang Tua: Konsep, Pengembangan, dan Validasi - Shanti, Theresia Indira; Suryani, Angela Oktavia; Ajisuksmo, Clara R.P. (Jurnal InterAct, 2020)
Perceived supportive communication by adolescence and emerging adulthood influence how they develop their autonomy and independency and in the same time still have opportunity to gain support from their parents when they need it. The aim of this study is to develop instrument that measure perceived parents’ supportive communication by adolescence and emerging adulthood. The instrument development consists of three stages: 1) Focus group discussion (FGD) to find out the description of perceived parents’ supportive communication (35 respondents from three universities). The result of this stage is the items of the instrument; 2) Validity and Reliability testing (326 respondents of high school and university students). The result of this stage is the valid and reliable instrument; 3) Factor Analysis from 600 respondents. The result of this stage is the dimentions of the instrument; dan 4) Confirmatory Factor Analysis (CFA) from 1065 respondents. The result of this stage is the same as final result of the whole study, that is perceived parents’ supportive communication instrument, which consists of two dimentions (empathy and confidentiality).